THE IMPACT OF PESTICIDE USE IN AGRICULTURE: THEIR BENEFITS AND HAZARDS - Lenara X. Elmurodova ,; Jasurbek D. Ummatov , (Central Asian Journal of Medicine, 2025)
Pesticides are widely used in agriculture to protect crops from pests and diseases, ensuring food security and economic stability. Despite their benefits, excessive and improper use poses serious environmental and health hazards. This article explores the historical development, production, and application of pesticides, particularly in Uzbekistan, where their use has been regulated since 1947. The study highlights the advantages of pesticides, such as increased agricultural productivity and disease control, while also addressing their harmful effects on human health and ecosystems.